2012
DOI: 10.1039/c1an15877e
|View full text |Cite
|
Sign up to set email alerts
|

Stable fluorescent gold nanoparticles for detection of Cu2+with good sensitivity and selectivity

Abstract: A simple and one-pot method for the synthesis of water-soluble, redemitting, highly fluorescent gold nanoparticles has been reported using 11-mercaptoundecanoic acid (11-MUA) as the protecting group. We found that the fluorescent gold nanoparticles could selectively detect copper ions in aqueous solution, with a limit of detection of about 87 nM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 55 publications
(6 reference statements)
4
61
0
Order By: Relevance
“…The results showed that the fluorescence intensity increased with increasing pH of solution up to a pH 7.4 and then remained more or less constant. This is because of deprotonation of Hb (with a pI of 6.8) on the surface of the Hb-AuNCs, at higher pHs, which resulted in repulsion among the fluorescent gold nanoclusters and thereby stabilizing system [27]. A measured zeta potential of −30.4±4.0 mV on Hb-AuNCs reflects such a great electrostatic repulsion between particles.…”
Section: Characterization Of Hb-auncsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the fluorescence intensity increased with increasing pH of solution up to a pH 7.4 and then remained more or less constant. This is because of deprotonation of Hb (with a pI of 6.8) on the surface of the Hb-AuNCs, at higher pHs, which resulted in repulsion among the fluorescent gold nanoclusters and thereby stabilizing system [27]. A measured zeta potential of −30.4±4.0 mV on Hb-AuNCs reflects such a great electrostatic repulsion between particles.…”
Section: Characterization Of Hb-auncsmentioning
confidence: 97%
“…3d, the corresponding plot of (F 0 /F) versus [Cu 2+ ] shows two excellent linear correlations graphs with \correlation coefficients (R 2 ) of 0.9973 and 0.9942, over the copper concentrations 0.1-1.0 μM and 1.0 to 20.0 μM, respectively. The LOD was calculated to be 28 nM (S/N=3), which is much lower than the safe limit of copper ions in drinking water (i.e., 1.3 ppm, 20 μM) established by the United States Environmental Protection Agency (EPA) [27].…”
Section: Signal-off Fluorescence Detection Of Cu 2+mentioning
confidence: 99%
“…Additionally, the paramagnetic feature of Cu 2? would also contribute to the emission quenching due to the generation of intersystem crossing process; thus, the transitions from excited states to ground states were reduced [23,24]. Furthermore, we have studied the correlation between the quenching effect (I 0 /I) and concentration of the guest species (F -or Cu 2? )…”
Section: Resultsmentioning
confidence: 98%
“…Fluorescent AuNPs could be utilized in sensors for the purpose of heavy metal detection, controlling the growth of pathogens, imaging, etc. [23][24][25][26][27][28]. Some methods have already been developed to prepare fluorescent AuNPs, such as reduction of gold precursor with NaBH 4 in the presence of 11-mercaptoundecanoic acid in toxic organic solvent, reduction of gold precursor with biomolecules like bovine serum albumin (BSA) and etching pre-synthesized AuNPs with hyperbranched and multivalent polymers [23,29,30].…”
Section: Structurementioning
confidence: 99%